Formation of basil seedlings for the extraction of essencial oil in different substrates - Galbiatti, João Antônio; Ariguchi, Bárbara Barofaldi; de Sousa, Cacilda Mendes; Caramelo, Anaira Denise; de Faria, Rogério Teixeira [UNESP] (My University, 2015)
Basil plants are cultivated in most Brazil in home gardens for spice, medicinal and ornamental uses. The present study aimed to evaluate different sources and combinations of substrates in the production of basil seedlings, through the development and production of essential oil grown in two water regimes. The experiment was conducted at the Experimental Station of Bebedouro-SP. Ten substrates were tested, resulting from the combination of commercial substrate, bovine manure, organic waste compost and organic tree pruning compost. The experimental design was randomized blocks with 20 treatments in a factorial 10 x 2 (10 substrates and 2 irrigation levels) experiment with 3 replicates. The amount of fresh matter and oil content produced in the basil leaves was evaluated. The fresh matter of the substrate 4 (60% of soil and 40% of manure) was satisfactory with 80% of evaporation. As for the substrate oil content, the substrates 4 (60% of soil and 40% of manure), 3 (60% of soil and 40% of waste compost) and 5 (60% of soil and 40% of pruning compound) were the highest oil producers, at 80% of the evapotranspiration.
Keywords: Ecological appeal; Organic compounds; Water regimes